The political economy of prosperity - Okun, Arthur M. (Washington : Brookings Institution, 1970)
The author wrote about the U.S. political economy of the sixties and the problem of sustaining national prosperity.
"The substance of this book was presented as the Crawley Memorial Lectures at the Wharton School of Finance and Commerce of the University of Pennsylvania in April 1969."
Bibliographical footnotes.
rpm 15/06/2017
Loans
Keywords: Economic stabilization; United States--Economic policy--1961-1971.; United States $1 (BEconomic policy $1 (B1953-s; United States $1 (BEconomic policy & plannings; United States